HUMANISM AS ANTI-IDEOLOGY - Gavrilov, Alexander (Surfaces, 2001)
Under Communist rule, Party ideology and humanistic values conflicted with one another. In analysing this conflict, the author underlines the theoretical resources and the great political assets of humanism. Communism was afflicted by its hypocrisy moving from the general the "Man is good" to the particular the "Men living in communism are good". However, scientific socialism and its state politics changed the country into a great reading hall where humanities, and among them philology, became very popular. Philology, as a tool in the study of style, is essentially ideology-proof. Rather than developing counter-ideologies, many Russians turned to an active passive resistance through uses of irony that the humanities cultivated. This praxis of gradually eroding the dominant ideology within oneself and one’s environment was necessary to what would become perestroika. Humanism has proven to be, under necessity, a marvelous opponent of ideology.